A relational database for the FGSC - K McCluskey (Fungal Genetics Reports, 2000)
In our continuing effort to make more information about the materials at the FGSC available, we have developed a new database for the FGSC. This database has information about strains, lesions and a limited amount of information about cloned genes. There are also links to Genbank listings for many genes that are represented in the collection. The new database also manages the FGSC customer list and allows us to track orders.